Neotype designation, redescription, biology and distribution of Acanthopsyche alstoni Watt & Mann, 1903 (Lepidoptera: Psychidae) from India - Usha, A. U.; Sobczyk, T.; Roby, T. J.; Jose, Joyce (Zootaxa, 2022)
Acanthopsyche alstoni Watt & Mann, is a lesser known psychid previously known only from the description of its larval cases collected from Assam, India in 1903. There were no descriptions of the adult moth or biology of the species. During surveys for Psychidae in the human inhabited regions of Kerala State, India, more than 100 larval cases were recovered. They were allowed to hatch and characteristics were recorded. This paper provides a detailed redescription of this species and designation of a neotype.